PENGGUNAAN KARTU “MATCH GAME FOR BILOKS” UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN PESERTA DIDIK KELAS X IPA2 MAN 10 JAKARTA - Yuliana Dwi Asworo (Balai Diklat Keagamaan Jakarta, 2020)
The difficulty of students remembering and understanding oxidation numbers (Biloks) and compound nomenclature of ionic compounds and kovalen compounds makes the teacher think how to make learning activities more fun and memorable so that learning material can be remembered by students. One way to increase quality of learning is using media. In this study the authors used Match Game for Biloks. This media is applied in the redoks chapter of the oxidation number and compound nomenclature in chemistry class X semester 2 and it can also refresh the memories of class XII first semester students before entering redox material. This innovation was tested in class X IPA2 MAN 10 Jakarta in the 2019/2020 academic year with 36 students consisting of 11 boys and 25 girls. The impact of the innovation to students learning activity and learning goals was observed through questionnaires and test. This game is inspired by domino games, where each player must pair the card he has with the previous card. The making this media by determining the 60 elements/compound/ion molecular formulas along with their names and the oxidation number of the elements to be asked are given different colors in the molecular formula after that make the card “match game”. After this media has finished that match games are played in groups and each group has a teacher assistant (expert student) who holds the answer key from the match game it has to correct the answer of their friends. This game uses certain rules by distributing 30 dominoes to the five students so that the winner of the students is the one who runs out first and gets the highest score.